Analisis Makna Referensial dan Struktural-Kognitif Ullmann untuk Penguatan Kompetensi Mahasiswa PBA - Lisnawati, Lisnawati; Susiawati, Iis (INCARE, International Journal of Educational Resources, 2025)
This study aims to analyze the application of Stephen Ullmann’s theories of referential and structural-cognitive meaning, as presented in Semantics: An Introduction to the Science of Meaning, within the teaching of Ilmu al-Dil?lah wa al-Ma??jim in the Arabic Language Education program. The research method employed is a literature study with a qualitative theoretical-conceptual approach, focusing on publications from 2020–2025. The findings indicate that the referential meaning theory plays a crucial role in training students to connect linguistic expressions with concrete realities, while the structural-cognitive theory enriches students’ understanding of semantic relations, connotations, cognitive associations, and the symbolism of the Arabic language. The integration of these two theories into the curriculum enables a more applicative approach to semantics, moving beyond normative instruction toward contextual and critical learning. Recent literature (Al Fajr et al., 2025; Umar & Hariyadi, 2025) affirms that this integrative approach enhances students’ skills in semantic analysis, cultural sensitivity, and practical competence in interpreting both classical and contemporary Arabic texts. Thus, the application of Ullmann’s theories is expected to serve as a foundation for developing the Ilmu al-Dil?lah wa al-Ma??jim curriculum, thereby strengthening the competencies of Arabic Language Education students comprehensively.